Analysis of the Legal Power of SKPT in Land Sale and Purchase Transactions in Paleleh District, Buol Regency - Moh. Yoenardi M. Basiman; Nirwan Junus; Sri Nanang Meiske Kamba (Estudiante Law Journal, 2023)
The purpose of this research is to find out the legal force of SKPT in land sale and purchase transactions in Paleleh District, Buol Regency. The research method used is empirical research, namely the author will seek and find information which will later be used as the substance of this research by means of observation or conducting field studies in the place that is used as the object of this research. this research is carried out in a planned and systematic manner to obtain answers to problem solving related to the problems that occur, especially regarding the existence of buying and selling transactions using Land Tenure Certificate (SKPT) in Paleleh District. The results of this research on the legal force of land ownership certificates in sale and purchase transactions in Paleleh Subdistrict, where many people in Paleleh Subdistrict conduct land sale and purchase transactions using only a Land Ownership Certificate.  This is due to the habits of people in rural areas who do not want to be complicated in thinking about the legal aspects of land sale and purchase transactions, for them it is enough just to provide receipts as proof that payment has been made.